Pomelo, a resistance variety to Citrus tristeza virus in peninsular Malaysia. - Ayazpour, Kavous; Sijam, Kamaruzaman; Vadamalai, Ganesan; Jaafar, Hawa Z. E. (2011)
Citrus tristeza virus (CTV) is the most important viral disease of Citrus and is distributed worldwide. Results of ELISA and PCR methods showed that all Citrus varieties including Fortunella sp., Citrofortunella microcarpa and Citromelo in major citrus growing areas of Malaysia were infected with CTV in a high rate. In most areas, pomelo however was free of infection, but in Cameron Highlands, we found some strains of CTV that were severe to Citromelo and pomelo. Phylogeny studies revealed that these strains were familiar to CTV isolates from China and Japan and were very differ from CTV isolates of USA and New Zealand.